Comparison of IL-2 vs IL-7/IL-15 for the generation of NY-ESO-1-specific T cells - Gong, Wenjie; Hoffmann, Jean-Marc; Stock, Sophia; Wang, Lei; Liu, Yibin; Schubert, Maria-Luisa; Neuber, Brigitte; Hückelhoven-Krauss, Angela; Gern, Ulrike; Schmitt, Anita; Müller-Tidow, Carsten; Shiku, Hiroshi; et al. (Cancer immunology immunotherapy, 2019)
The anti-tumor efficacy of TCR-engineered T cells in vivo depends largely on less-differentiated subsets such as T cells with naïve-like T cell (TN) phenotypes with greater expansion and long-term persistence. To increase these subsets, we compared the generation of New York esophageal squamous cell carcinoma-1 (NY-ESO-1)-specific T cells under supplementation with either IL-2 or IL-7/IL-15. PBMCs were transduced with MS3II-NY-ESO-1-siTCR retroviral vector. T cell generation was adapted from a CD19-specific CART cell production protocol. Comparable results in viability, expansion and transduction efficiency of T cells under stimulation with either IL-2 or IL-7/IL-15 were observed. IL-7/IL-15 led to an increase of CD4+ T cells and a decrease of CD8+ T cells, enriched the amount of TN among CD4+ T cells but not among CD8+ T cells. In a 51Cr release assay, similar specific lysis of NY-ESO-1-positive SW982 sarcoma cells was achieved. However, intracellular cytokine staining revealed a significantly increased production of IFN-γ and TNF-α in T cells generated by IL-2 stimulation. To validate these unexpected findings, NY-ESO-1-specific T cell production was evaluated in another protocol originally established for TCR-engineered T cells. IL-7/IL-15 increased the proportion of TN. However, the absolute number of TN did not increase due to a significantly slower expansion of T cells with IL-7/IL-15. In conclusion, IL-7/IL-15 does not seem to be superior to IL-2 for the generation of NY-ESO-1-specific T cells. This is in sharp contrast to the observations in CD19-specific CART cells. Changes of cytokine cocktails should be carefully evaluated for individual vector systems.